Parametric analysis for the implementation of wind power in United Arab Emirates - Al-Tajer, Yaseen; Poullikkas, Andreas (My University, 2015)
In this work, the utilization of different wind turbines in a 50 MW wind park is tested, using annual hourly values of wind speeds in the Emirate of Sharjah in the United Arab Emirates. An optimization algorithm is developed in order to calculate the power output from 16 different wind turbine types with various capacities. Output data from the developed algorithm is used as input to the IPP optimization software in which the electricity unit cost is calculated. Also, parametric analyses regarding the cost of electricity production with respect to the capital costs of the wind turbines, as well as the cost of electricity production with respect to fixed costs are carried out. The power output from 5 wind parks during a stagnant and a windy day are determined. It is concluded that the utilization of fifty 1 MW wind turbines is the best option, as it presented the highest capacity factor, and the least cost of electricity production.
Keywords: Energy economics; Renewable energy sources; Wind energy